2000
DOI: 10.1016/s0735-1097(00)00817-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet effects of clopidogrel compared with aspirin after myocardial infarction: enhanced inhibitory effects of combination therapy

Abstract: Clopidogrel alone or in combination with aspirin markedly inhibited adenosine diphosphate (ADP)-mediated platelet aggregation compared with monotherapy with aspirin (24.6 +/- 3.3% or 26.6 +/- 2.7% vs. 44.7 +/- 2.9%; p < 0.001). Combined treatment significantly inhibited collagen-induced aggregation compared with aspirin and clopidogrel (16.4 +/- 2.4%, 36.5 +/- 4.2% and 59.3 +/- 5.1%, respectively;, p < 0.001) and resulted in considerable inhibition of aggregation induced by thrombin receptor agonist peptide (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 29 publications
5
107
1
2
Order By: Relevance
“…Clopidogrel and aspirin synergistically inhibit platelet function through two different pathways: the P2Y 12 subtype ADP receptor for clopidogrel and the cyclooxygenase-1 enzyme for aspirin (16,17). The addition of clopidogrel to aspirin was accompanied by a significant reduction in platelet aggregation compared with baseline values; however, this still resulted in suboptimal platelet inhibition in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel and aspirin synergistically inhibit platelet function through two different pathways: the P2Y 12 subtype ADP receptor for clopidogrel and the cyclooxygenase-1 enzyme for aspirin (16,17). The addition of clopidogrel to aspirin was accompanied by a significant reduction in platelet aggregation compared with baseline values; however, this still resulted in suboptimal platelet inhibition in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, rather than an additive effect, the two drugs used together were synergistic [22,23]. A potent synergism between clopidogrel and anticoagulants [using either a direct thrombin inhibitor (Bivalirudin), a FXa inhibitor or a synthetic LMW heparin] has also been observed ( Fig.…”
Section: Combination Antithrombotic Therapymentioning
confidence: 97%
“…However as shown in table 2, the performance of the tests is subject to considerable variation, which may affect the results. The variation in agonist concentration may influence the results obtained by optical platelet aggregation, since Moshfegh et al (2000) have demonstrated a clear dose-response relationship ( fig. 4) between the concentration of agonist used and the degree of aggregation measured.…”
Section: Important Bias Potentially Affecting Interpretation!mentioning
confidence: 99%